Academic Senate Minutes 2006-03-23 - Academic Senate:::::::::
Chair's Report. Agenda amended and approved. Consultation Policies postponed. Resolution on the Green Music Center approved. Resolution on Censorship at Dominquez Hill approved. Priority Registration Policy approved. Resolution on Faculty Workload referred to FSAC. Provost's Report. Good of the Order.